STUDENTS' PERCEPTIONS OF POMODORO STUDY TECHNIQUE FOR ENGLISH LEARNING HABITS IN ENGLISH COURSE OF UKIR VILLAGE - Aniqotul Chalimah; Slamet Utomo; Agung Dwi Nurcahyo (Prominent, 2023)
Abstract: This study focuses on investigating the students' perceptions of the Pomodoro study technique and how the Pomodoro study technique influences students' English learning habits. Pomodoro study technique is a study technique that uses a timer to break down work into intervals. To find out the answers for research purposes, a semi-structured interview and Likert-scale questionnaire were used. After analyzing and interpreting the data the finding shows that the students perceive the Pomodoro study technique as an effective technique to improve their English learning habits. Some aspects of the students’ learning habits that have been improved are their focus, discipline, concentration, productivity, and motivation. Also, in their opinion, the rules of the Pomodoro study technique were easy to follow. The finding from the Likert-scale questionnaire shows that the Pomodoro study technique improves and influences most students' learning habits indicators. The indicators are time management, concentration, discipline, self-control, and self-improvement. Based on the questionnaire result, the range agree has the highest number of responses which is 47. The results demonstrate that the Pomodoro study technique improves the students' learning habits, so it can be said that the Pomodoro study technique is effective. The indication of the conclusion is based on the descriptive rating scale.